Human Resource Development Analysis Using SOAR Analysis and QSPM Analysis (Case Study at CV. Mustika Digdaya) - Deviyanti, I Gusti Ayu Sri; Widari, Nyoman Sri; Fais, Moh. Ainul (Jurnal Optimalisasi, 2025)
The purpose of this research is to explain the process of training and developing human resources at the Fan Sate soy sauce factory in Probolinggo Regency. The sources of information in this study were factory owners and workers. The methods used in this study are qualitative–descriptive methods using data collection techniques in the form of observation, interviews, transportation, and documentation. The analysis results found that the Fan Sate soy sauce factory applied several methods in employee training, such as learning methods, work instruction training, and work training. As for employee development, the Fan Sate soy sauce factory uses job rotation and training methods. The research uses SOAR (Strengths, Opportunities, Aspirations, Results) and QSPM (Quantitative Strategic Planning Matrix) analysis. The development of mentorship or coaching programs has become an important strategy in improving the leadership and skills of employees in various organizations. Through mentorship or coaching relationships, employees get insights and feedback directly from an experienced mentor or coach, which can accelerate their learning process and improve their performance. Thus, the program is not only beneficial to the individuals involved but also has a positive impact on the entire organization.